CHINESE RETAIL MARKET: REAL POTENTIAL TO BECOME THE GREATEST WORLDWIDE BEFORE 2020 - ECATERINA STǍNCULESCU (Global Economic Observer)
The present article tries to capture current market developments of the Chinese retail sales in the last 4-5 years, emphasising its tendency to become the first global market before 2020. The author makes a brief analysis of the Chinese retail market sales characteristics including growth rates, sales structure, influencing factors (population growing income, urbanization, consumer goods imports). The characteristics of the constantly changing retail consumer market and the main challenges faced by the trans-national companies activating on the Chinese market represent distinct points in the analysis undertaken in this article.